Experimental investigation of the impact of tidal turbine blade design on performance in turbulent flow - Smyth, ASM; Young, AM; Gaurier, B; Germain, G (Technical Committee of the European Wave and Tidal Energy Conference, 2021)
The nature of tidal channel flows presents unique challenges to tidal turbine designers due to the high levels of unsteady flow from large-scale ocean turbulence. This causes fluctuating loads on the turbine blades, leading to integrity and performance issues. This paper outlines an experimental campaign performed in order to assess whether turbine blade design can be used to improve performance in unsteady flow conditions, potentially reducing the fluctuating loads, and increasing turbine lifetime as a result. Two turbines, one with low-TSR, high-solidity blades (T4) and one with high-TSR, low-solidity blades (T7), are tested in a recirculating water flume in low and high turbulence flow. It is confirmed that the two turbine designs produce the same mean power coefficient at their respective design TSRs (given similar Reynolds numbers). Relative to their performance in clean flow, the mean power coefficient of T4 increases in high-turbulence flow (I = 15%), while the mean thrust coefficient for T7 decreases. The root-mean-square fluctuations in power and thrust are similar between the two turbines. In the torque and thrust response spectra of the two turbines, a dynamic region of response to turbulence is identified. This dynamic response is found to be strongly correlated to turbine rotational frequency. In the dynamic response region, T7 is found to respond more strongly to turbulence at multiples of the blade-passing frequency compared to T4. This suggests that T7 may be more sensitive to turbulent flow than T4, but further study is needed to determine whether this results only from the higher TSR, or if the low solidity of the T7 blades also has an impact.